Palladium‐Catalyzed ortho‐Selective CH Deuteration of Arenes: Evidence for Superior Reactivity of Weakly Coordinated Palladacycles1. (29th November 2013) - Ma, Sandy; Villa, Giorgio; Thuy‐Boun, Peter S.; Homs, Anna; Yu, Jin‐Quan
Abstract We disclose a protocol for the palladium‐catalyzed ortho‐selective CH deuteration of arenes. Phenylacetic acids and benzoic acids are suitable substrates for this reaction. This reaction offers a catalytic route to ortho‐deuterated phenylacetic acids and benzoic acids and demonstrates the sharp difference in reactivity of palladacycle intermediates held together by weak and strong coordination.